2012
DOI: 10.1002/cctc.201200106
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization and Dimerization of Pinene using Al‐Incorporated MCM‐41 Mesoporous Materials

Abstract: A series of Al‐incorporated mobile crystalline materials (Al‐MCM‐41) were prepared by hydrothermal synthesis and characterized by XRD, N2 adsorption (isotherms), inductively coupled plasma (ICP) analysis, 27Al magic angle spinning (MAS) NMR spectroscopy, and in situ pyridine adsorption (IR analysis). All samples exhibit an ordered structure with the majority of Al species in framework positions, except those with an SiO2/Al2O3 ratio ≤10. The concentration of acid sites is closely related to the Al content in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 38 publications
3
41
0
Order By: Relevance
“…Despite the mild reaction conditions of this industrial process, its low conversion and selectivity requires significant advances to improve both atom and energy efficiency. A wide range of alternative catalysts have been explored including alloys, [14] clays, [18,19] zeolites, [20,21] sulphated zirconia, [16,22], Al-incorporated MCM-41 [23] and heteropolyacids (HPAs); [24][25][26][27][28] with strong solid acids conferring improved conversion and selectivity. [21,22,24,27,29] HPAs are polyoxometalate inorganic cages which possess high Brönsted acid strengths (approaching the superacidic region) and tunable redox activity depending on the particular constituent elements.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the mild reaction conditions of this industrial process, its low conversion and selectivity requires significant advances to improve both atom and energy efficiency. A wide range of alternative catalysts have been explored including alloys, [14] clays, [18,19] zeolites, [20,21] sulphated zirconia, [16,22], Al-incorporated MCM-41 [23] and heteropolyacids (HPAs); [24][25][26][27][28] with strong solid acids conferring improved conversion and selectivity. [21,22,24,27,29] HPAs are polyoxometalate inorganic cages which possess high Brönsted acid strengths (approaching the superacidic region) and tunable redox activity depending on the particular constituent elements.…”
Section: Introductionmentioning
confidence: 99%
“…For example, for the production of the monoterpene dimer jet fuel described above, three enzymes were tested from among the 11 that were known to produce β-pinene, all of which came from plants (Degenhardt et al 2009; Sarria et al 2014). Several other dimerization strategies have been reported that have utilized both α and β pinene (Chen and Forbus Jr 1990; Booth and Phillips Jr 1998; Chapaton et al 2004; Zou et al 2012). Filamentous fungi have been observed to produce both α and β pinene, though α is considerably more common (Table 1).…”
Section: Jet Fuel Surrogatesmentioning
confidence: 99%
“…In recent years, the use of heterogeneous catalyst is a shi toward green and environmental-friendly technologies. Various solid acid catalysts, such as zeolites, 3,4 iron-modied zeolites, 5 sulfated zirconia, 6 modied layered aluminosilicates, 7 Al-incorporated MCM-41, 8 MSU-S mesoporous materials, 9 W 2 O 3 /Al 2 O 3 , 10 phosphotungstic heteropoly acids, 11 Ti-SBA-15 (ref. 12 and 13), and ionic liquids 12 have been employed for the isomerization of a-pinene.…”
Section: Introductionmentioning
confidence: 99%